Advanced maternal age and late pregnancy outcome at Omdurman New Hospital in Sudan - Ahmed, Khalid; Ahmed, Shireen; Handady, Siddig; Alawad, Awad; Ali, Sulafa (International Journal of Medicine, 2015)
Background: Advanced Maternal age has a 2–3 fold higher risk of pregnancy-related death than women in their twenties, and the risk is even more dramatic for women 40 years and older.Objective: The overall aim was to examine the association between maternal age and a wide range of adverse pregnancy outcomes.Methodology: This is a case-control hospital-based study carried out at Omdurman New Hospital in Khartoum State, Sudan in the period from July 2013 to January 2014. Three hundred women presented in labour were enrolled in this study. One hundred women at 40 years age or more presented after 24th week of pregnancy represented the study group. Two hundred women between 18-39-year age; same gestational ages were selected as the control group.Results: The mean of age was 42±2 STD (min 40 and max 45 years) among the case group, and it was 27±2 STD (min 20 and max 39 years) among the case group. Women aged 40 years or older had increased percentages of gestational hypertension (23.0% vs. 13.5%; p=0.03) and diabetes in pregnancy (8.0% vs. 4.0%; p=0.03) compared with women younger than 40 years. There were significant differences between the two age groups in, antepartum hemorrhage, preterm labor, and premature rupture of membranes, perinatal death, and postpartum hemorrhage. Vaginal delivery in case group was 53 (53%) against 127 (63.5%) in control group, caesarean section found in 47 (47%) of case group against 36.5% of control group, instrumental found in one patient (1%) of case group and it was absent in control group.Conclusion: Advanced maternal age is a risk factor for premature rupture of membranes, preterm labour, pre-eclampsia, stillbirth, gestational diabetes mellitus, placenta previa, abruptio placentae and cesarean section, but not for small for gestational age, gestational hypertension, or large for gestational age.